Emulsion cross-linking method for preparing boron nitride nanosheet microspheres
The preparation of boron nitride nanosheet microspheres through improved emulsification and cross-linking method has solved the problems of high energy consumption, high cost and low thermal conductivity in the existing process, and achieved a simple process, low energy consumption and low cost high thermal conductivity nanosheets with simple technology, low energy consumption and low cost Microsphere preparation, suitable for electronic packaging.
Patent Information
- Application Number
- CN202410852038.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-28
- Publication Date
- 2025-02-18
AI Technical Summary
The existing boron nitride microsphere preparation process has problems such as high energy consumption, high cost and low thermal conductivity, and it is difficult to obtain a high solids content and stable emulsion.
Pre-oxidized boron nitride nanosheets are used as raw materials and granulated by improved emulsification cross-linking method, including mixing emulsifier with liquid paraffin, adding dispersant with pre-oxidized boron nitride nanosheets sodium alginate solution, stirring emulsification, and adding Crosslinking agent, reaction crosslinking, standstill, centrifuge, dry, glue discharge and sintering to prepare boron nitride nanosheet microspheres.
Achieve simple process, low energy consumption and low cost preparation of boron nitride nanosheets, improve the dispersion and solid content of BN nanosheets in the aqueous phase slurry, and prepare an average particle size of 30-400μm and an average sheet size of 2- BN nanosheet microspheres with an average sheet thickness of 50-100 nm are suitable for high thermal conductivity fillers for electronic packaging.
Smart Images

Figure CN119461267A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of heat-conducting and insulating inorganic non-metallic materials, and is a method for preparing boron nitride nanosheet microspheres. Background Art
[0002] Hexagonal boron nitride is an inorganic non-metallic material with high thermal conductivity. It has excellent lubrication properties, stable chemical properties, strong oxidation resistance, chemical corrosion resistance, and excellent dielectric properties. When used as a thermal conductive filler, boron nitride will increase the polymerization viscosity, reduce the filling amount, and easily agglomerate due to its flaky structure, which is not conducive to uniform dispersion. The amount of spherical boron nitride powder added to the polymer is significantly increased compared to lamellar boron nitride powder, and a 3D thermal conductive network can be constructed through the grading of microspheres of different particle sizes, greatly improving the thermal conductivity of the composite material.
[0003] The existing process for preparing BN microspheres is generally a spray granulation method, which has the problem of low heat utilization efficiency. Most of its energy is lost through hot air exhaust, resulting in high energy consumption and high preparation cost. An existing patent (CN 103395752 A) discloses a method for preparing boron nitride micron solid spheres, which uses trichloroborazine and toluene as basic raw materials to prepare a polymerized trichloroborazine precursor; then, at 1400°C, 0.3-3MPa high-pressure nitrogen atmosphere, the boron nitride micron solid spheres are cracked. The raw materials and cracking products of this scheme contain a large amount of substances that are toxic to the environment, and the process operation is complicated. When preparing BN microspheres by conventional emulsification cross-linking method, due to its flaky structure and hydrophobicity, it is impossible to obtain a high solid content and stable emulsion, and it is difficult to prepare BN microspheres. In addition, existing BN microsphere products are usually composed of sintered BN grains with an average sheet thickness of micrometers. The thermal conductivity of BN in the direction of the average sheet thickness is two orders of magnitude lower than the in-plane thermal conductivity, resulting in the overall thermal conductivity of the BN microspheres being low, making it difficult to fully utilize their high thermal conductivity advantages.
[0004] Therefore, the present invention uses high thermal conductivity boron nitride nanosheets as raw materials and granulates them through an improved emulsification crosslinking method, which has the advantages of simple process and low energy consumption preparation cost. The prepared boron nitride nanosheet microspheres can be used as high thermal conductivity fillers for electronic packaging. Summary of the invention
[0005] The present invention introduces a method for preparing boron nitride nanosheet microspheres, comprising the following steps:
[0006] The emulsifier and liquid paraffin are mixed and stirred to obtain an oil phase: a dispersant and pre-oxidized boron nitride nanosheets are added to a sodium alginate solution to obtain an aqueous phase, which is stirred and emulsified, and a calcium chloride solution is used as a cross-linking agent, and the reaction is cross-linked, allowed to stand, centrifuged, dried, and debonded, and the boron nitride nanosheet microspheres are sintered in a nitrogen atmosphere.
[0007] Furthermore, the mass fraction of sodium alginate to pre-oxidized boron nitride nanosheets is 0.75-3%, and the concentration of calcium chloride solution is 50 mg / ml. The mass fraction of emulsifier to aqueous phase is 1-6%. The average sheet size of boron nitride nanosheets is less than 2 μm, the average sheet thickness is less than 50 nm, and the oxygen content of pre-oxidized boron nitride nanosheets is 1-3%. The mass fraction of dispersant to pre-oxidized boron nitride nanosheets is 2-8%. The dispersion method is centrifugal dispersion in a vacuum defoamer. The stirring speed of the emulsification process is 150-600 r / min, and the time is 1-2h. The amount of calcium chloride solution added is 40 ml. The stirring time of the cross-linking process is 1-2h. The debinding temperature is 600°C, and the sintering temperature is 1500-1600°C.
[0008] The invention provides a method of using pre-oxidized boron nitride nanosheets as raw materials, granulating and forming by an improved emulsification crosslinking method, improving the dispersibility and solid content of BN nanosheets in water phase slurry, and sintering to prepare BN nanosheet microspheres with an average particle size of 30-400 μm, an average sheet size of 2-10 μm, and an average sheet thickness of 50-100 nm. The preparation method has the advantages of simple process, low energy consumption and preparation cost, and the prepared boron nitride nanosheet microspheres can be used as high thermal conductivity fillers for electronic packaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 The SEM image of boron nitride nanosheet microspheres obtained in Example 1 of the present invention;
[0010] Figure 2 The SEM image of boron nitride nanosheet microspheres obtained in Example 2 of the present invention;
[0011] Figure 3 This is a SEM image of boron nitride nanosheet microspheres obtained in Example 5 of the present invention; DETAILED DESCRIPTION
[0012] Example 1
[0013] The method for preparing the boron nitride nanosheet microsphere thermal conductive filler according to the embodiment of the present invention comprises the following steps:
[0014] 1g of Span-80 was added to 99g of liquid paraffin and stirred to obtain an oil phase solution. 0.5g of sodium alginate was added to 99.5ml of deionized water heated at 85°C in a water bath and stirred to obtain a sodium alginate solution. 6.25g of boron nitride nanosheets with an oxygen content of 2% were added to 18.625g of the sodium alginate solution, and 0.125g of Tween-80 was added to the mixture and centrifuged and mixed evenly in a vacuum defoamer to obtain an aqueous suspension. 25g of the aqueous suspension was added dropwise to 100g of the oil phase solution, stirred and emulsified at a speed of 400r / min, and then 40ml of a 50mg / ml calcium chloride solution was added dropwise, the reaction was cross-linked for 1h, the mixture was allowed to stand, centrifuged, dried, and debonded, and the boron nitride nanosheet microspheres were obtained by sintering at 1550°C for 4h under a nitrogen atmosphere.
[0015] The sample was characterized by a laser particle size analyzer. The average particle size of the boron nitride nanosheet microspheres was 60.3 μm. The sample was characterized by a scanning electron microscope. The average sheet size of the boron nitride nanosheet microspheres was 6.3 μm and the average sheet thickness was 84 nm. The SEM image is shown in Figure 1 shown.
[0016] Example 2
[0017] The method for preparing the boron nitride nanosheet microsphere thermal conductive filler according to the embodiment of the present invention comprises the following steps:
[0018] 1g of sodium alkyl sulfonate was added to 99g of liquid paraffin and stirred to obtain an oil phase solution. 0.5g of sodium alginate was added to 99.5ml of deionized water heated at 85°C in a water bath and stirred to obtain a sodium alginate solution. 6.25g of boron nitride nanosheets with an oxygen content of 2% were added to 18.625g of the sodium alginate solution, and 0.125g of sodium dodecyl sulfate was added and centrifuged in a vacuum defoamer to mix uniformly to obtain an aqueous suspension. 25g of the aqueous suspension was added dropwise to 100g of the oil phase solution, stirred and emulsified at a speed of 300r / min, and then 40ml of 50mg / ml calcium chloride solution was added dropwise, the reaction was crosslinked for 1.5h, and the reaction was allowed to stand, centrifuged, dried, and debonded. Boron nitride nanosheet microspheres were obtained by sintering at 1600°C for 4h under a nitrogen atmosphere.
[0019] The sample was characterized by a laser particle size analyzer, and the average particle size of the boron nitride nanosheet microspheres was 100.2 μm. The sample was characterized by a scanning electron microscope (SEM), and the average sheet size of the boron nitride nanosheet microspheres was 5.8 μm and the average sheet thickness was 96 nm. The SEM image is shown in Figure 2 shown.
[0020] Example 3
[0021] The method for preparing the boron nitride nanosheet microsphere thermal conductive filler according to the embodiment of the present invention comprises the following steps:
[0022] 1.5g of polysorbate was added to 98.5g of liquid paraffin and stirred to obtain an oil phase solution. 0.33g of sodium alginate was added to 99.67ml of deionized water heated at 85°C in a water bath and stirred to obtain a sodium alginate solution. 6.25g of boron nitride nanosheets with an oxygen content of 1% were added to 18.625g of the sodium alginate solution, and 0.125g of methyl amyl alcohol was added to the mixture and centrifuged and mixed uniformly in a vacuum defoamer to obtain an aqueous suspension. 25g of the aqueous suspension was dropwise added to 100g of the oil phase solution, stirred and emulsified at a speed of 500r / min, and then 40ml of a 50mg / ml calcium chloride solution was dropwise added, the reaction was cross-linked for 2h, the mixture was allowed to stand, centrifuged, dried, and debonded, and the boron nitride nanosheet microspheres were obtained by sintering at 1500°C for 4h under a nitrogen atmosphere.
[0023] The sample was characterized by a laser particle size analyzer, and the average particle size of the boron nitride nanosheet microspheres was 30.8 μm. The sample was characterized by a scanning electron microscope (SEM), and the average sheet size of the boron nitride nanosheet microspheres was 3.4 μm and the average sheet thickness was 63 nm.
[0024] Example 4
[0025] The method for preparing the boron nitride nanosheet microsphere thermal conductive filler according to the embodiment of the present invention comprises the following steps:
[0026] 1g of Span-80 was added to 124g of liquid paraffin and stirred to obtain an oil phase solution. 1g of sodium alginate was added to 99ml of deionized water heated at 85°C in a water bath and stirred to obtain a sodium alginate solution. 6.25g of boron nitride nanosheets with an oxygen content of 2% were added to 18.625g of the sodium alginate solution, and 0.125g of Tween-80 was added and centrifuged in a vacuum defoamer to mix uniformly to obtain an aqueous suspension. 25g of the aqueous suspension was added dropwise to 125g of the oil phase solution, stirred and emulsified at a speed of 300r / min, and then 40ml of 50mg / ml calcium chloride solution was added dropwise, and the reaction crosslinking was carried out for 1.5h, and the reaction was allowed to stand, centrifuged, dried, and debonded. Boron nitride nanosheet microspheres were obtained by sintering at 1550°C for 4h under a nitrogen atmosphere.
[0027] The sample was characterized by a laser particle size analyzer, and the average particle size of the boron nitride nanosheet microspheres was 194.8 μm. The sample was characterized by a scanning electron microscope (SEM), and the average sheet size of the boron nitride nanosheet microspheres was 7.5 μm and the average sheet thickness was 85 nm.
[0028] Example 5
[0029] The method for preparing the boron nitride nanosheet microsphere thermal conductive filler according to the embodiment of the present invention comprises the following steps:
[0030] 0.25g of Span-80 was added to 99.75g of liquid paraffin and stirred to obtain an oil phase solution. 0.5g of sodium alginate was added to 99.5ml of deionized water heated at 85°C in a water bath and stirred to obtain a sodium alginate solution. 6.25g of boron nitride nanosheets with an oxygen content of 3% were added to 18.625g of the sodium alginate solution, and 0.125g of Tween-80 was added to the mixture and centrifuged and mixed uniformly in a vacuum defoamer to obtain an aqueous suspension. 25g of the aqueous suspension was dropwise added to 100g of the oil phase solution, stirred and emulsified at a speed of 200r / min, and then 40ml of a 50mg / ml calcium chloride solution was dropwise added, the reaction was cross-linked for 1.5h, the mixture was allowed to stand, centrifuged, dried, and debonded, and the boron nitride nanosheet microspheres were obtained by sintering at 1550°C for 4h under a nitrogen atmosphere.
[0031] The sample was characterized by a laser particle size analyzer, and the average particle size of the boron nitride nanosheet microspheres was 355.3 μm. The sample was characterized by a scanning electron microscope (SEM), and the average sheet size of the boron nitride nanosheet microspheres was 8.2 μm and the average sheet thickness was 82 nm. The SEM image is shown in Figure 3 shown.
[0032] Some embodiments
[0033] The effect of the solid content of boron nitride nanosheets on the microsphere morphology was examined, that is, the method and steps were the same as in Example 2. The solid content of boron nitride nanosheets and the microsphere morphology characteristics are shown in Table 1 below.
[0034] Table 1 Effect of solid content of boron nitride nanosheets on microsphere morphology
[0035] Instance number Boron nitride nanosheet solid content (%) Microsphere morphology 1 10 Loose powder, no microspheres 2 15 Loose powder, no microspheres 3 20 Spherical morphology 4 25 Spherical morphology 5 30 Spherical morphology 6 35 Irregular aggregates
[0036] Conclusion: When the solid content of boron nitride nanosheets is less than 20%, the product is loose powder without microspheres. When the solid content of boron nitride nanosheets is greater than 30%, the viscosity of the aqueous phase is too high, and irregular agglomerate particles are obtained. Therefore, the preferred solid content of boron nitride nanosheets is 20-30%.
[0037] Some embodiments
[0038] The effect of the amount of sodium alginate added on the particle size of the microspheres was examined, that is, the method steps were the same as Example 2, and the specific process parameters and particle size results are shown in Table 2 below.
[0039] Table 2 Effect of different sodium alginate addition amounts on microsphere particle size
[0040] Sample No. Sodium alginate addition amount (%) Particle size D50(μm) 1 0.50 Loose powder, no microspheres 2 0.75 50.4 3 1.25 56.4 4 1.50 100.2 5 2.25 88.9 6 3.00 60.1 7 4.00 Irregular agglomerate particles
[0041] Conclusion: When the addition amount of sodium alginate increases, the particle size increases first and then decreases. When the addition amount of sodium alginate is 1.50%, the particle size is the largest. When the addition amount of sodium alginate is less than 0.75%, loose powder without microspheres is produced. When the addition amount of sodium alginate is greater than 3.0%, the viscosity of the aqueous phase is too high to produce irregular agglomerate particles. When the addition amount of sodium alginate is 0.75-3.00%, microspheres with good strength and good sphericity can be obtained.
[0042] Some embodiments
[0043] The effect of the oxygen content of boron nitride nanosheets on the morphology of microspheres was examined. That is, the method and steps were the same as those in Example 4. The oxygen content of the boron nitride nanosheets and the morphology characteristics of the boron nitride nanosheets after sintering are shown in Table 3 below.
[0044] Table 3 Effect of oxygen content of boron nitride nanosheets on the morphology of sintered boron nitride nanosheets
[0045]
[0046]
[0047] Conclusion: As the oxygen content of boron nitride nanosheets increases, the average sheet thickness and size of the morphology of boron nitride after sintering tend to increase. When the oxygen content of boron nitride nanosheets is less than 0.5%, the effect of oxygen content on the modification of boron nitride nanosheets is not obvious, and the solid content is not significantly increased. When the oxygen content of boron nitride nanosheets is greater than 3%, the average sheet thickness of boron nitride after sintering is too large, and the high thermal conductivity advantage of boron nitride nanosheets cannot be exerted. Therefore, the oxygen content of pre-oxidized boron nitride nanosheets at 1-3% can increase the solid content of boron nitride nanosheets in sodium alginate solution.
[0048] Some embodiments
[0049] The effect of sintering temperature on the morphology of microspheres was examined. That is, the method steps were the same as those in Example 4. The sintering temperature and the morphology characteristics of the boron nitride nanosheets after sintering are shown in Table 4.
[0050] Table 4 Effect of sintering temperature on the morphology of sintered boron nitride nanosheets
[0051] Instance number Sintering temperature(℃) Average lamella thickness (nm) Average flake size (μm) 1 1400 50 2.3 2 1500 75 5.8 3 1600 96 8.6 4 1700 123 12.1
[0052] Conclusion: With the increase of sintering temperature, the average sheet thickness and size of the morphology of the sintered boron nitride tend to increase. When the sintering temperature is less than 1500℃, the grain growth of the boron nitride nanosheets is not obvious, and the small average sheet size is not conducive to the improvement of thermal conductivity. When the sintering temperature is greater than 1600℃, the average sheet thickness of the sintered boron nitride is too large, which is not conducive to the high thermal conductivity advantage of the boron nitride nanosheets. Therefore, the sintering temperature is 1500-1600℃, and the boron nitride nanosheets with an average sheet thickness of less than 100nm can be obtained.
[0053] Some embodiments
[0054] The process parameters of different microsphere particle sizes were tested, that is, the method steps were the same as Example 3, and the specific process parameters and particle size results are shown in Table 5 below.
[0055] Table 5 Process parameters of microspheres with different particle sizes
[0056] Instance number Stirring speed (r / min) Addition amount of Siban 80 (%) Sodium alginate addition amount (%) Particle size D50(μm) 1 150 1 1.5 Agglomerate particles 2 200 1 3.0 432.8 3 300 2 3.0 210.5 4 300 3 3.0 134.5 5 300 4 1.0 50.8 7 600 6 1.0 30.25
[0057] Conclusion: Boron nitride nanosheet microspheres with an average particle size of 30-400μm can be obtained by adjusting the process parameters. When the emulsification stirring speed is increased to more than 500r / min, the particle size of the microspheres does not decrease significantly. When the emulsification stirring speed is reduced to less than 150r / min, the boron nitride microspheres agglomerate and the molding fails due to the slow speed. Therefore, boron nitride nanosheet microspheres with an average particle size of 30-400μm can be obtained by adjusting the process parameters.
[0058] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing boron nitride nanosheet microspheres, characterized in that: The following steps are involved: Boron nitride nanosheets are added to a sodium alginate solution using a dispersant to prepare a water phase, liquid paraffin is used as an oil phase, an emulsifier is added, and the mixture is stirred and emulsified. A calcium chloride solution is used as a cross-linking agent, and the mixture is cross-linked by reaction, allowed to stand, centrifuged, dried, and debonded. The mixture is sintered in a nitrogen atmosphere to obtain boron nitride nanosheet microspheres with an average particle size of 30-400 μm, an average sheet size of 2-10 μm, and an average sheet thickness of 50-100 nm.
2. The method for preparing boron nitride nanosheet microspheres according to claim 1, characterized in that: The boron nitride nanosheet raw material has an average sheet size of less than 2 μm, an average sheet thickness of less than 50 nm, and an oxygen content of 1-3%.
3. The method for preparing boron nitride nanosheet microspheres according to claim 1, characterized in that The emulsifier is one or more of sodium alkyl sulfonate, polysorbate, and Span-80, and the dispersant is one or more of Tween-80, sodium lauryl sulfate, and methyl amyl alcohol.
4. The method for preparing boron nitride nanosheet microspheres according to claim 1, characterized in that The solid content of the boron nitride nanosheets in the suspension B is 20-30%.
5. The method for preparing boron nitride nanosheet microspheres according to claim 1, characterized in that: The gas introduced during high temperature sintering is nitrogen, and the sintering temperature is 1500-1600℃.
Citation Information
Patent Citations
Preparation method for boron nitride micron solid ball
CN103395752A